2006
DOI: 10.1021/ol060866v
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-Fesulphos Lewis Acid Catalysts for Enantioselective Mannich-Type Reaction of N-Sulfonyl Imines

Abstract: [reaction: see text] Copper(I) complexes of Fesulphos ligands are efficient chiral Lewis acid catalysts in the Mannich-type addition of silyl enol ethers of ketones, esters, and thioesters to N-(2-thienyl)sulfonyl aldimines. The corresponding optically active beta-amino carbonyl derivatives were obtained in good yields (58-91%) and with moderate to good enantioselectivity (61-93% ee). Removal of the N-activating group was achieved under mild conditions by simple treatment of the products with Mg in methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…(11) ( 12) N -Sulfonylaldimines undergo Mannich-type addition to silyl enol ethers of ketones, giving β-amino carbonyl derivatives in up to 93% ee in the presence of a chiral ee ferrocene bearing S-and P -substituents complexed to copper(II). 29 β-Aminocarbonyl compounds have been prepared via Lewis base-catalysed Mannich reaction of TMS enol ethers and N -tosylaldimines, ArCH=N−Ts, with excellent de anti selectivity in some cases. 30 A zinc-bis(BINOL) complex has been employed to effect chemoselective enolate de formation from an α-hydroxy ketone (in the presence of an isomerizable imine) to give a Mannich-type product in high ee.…”
Section: The Mannich Reactionmentioning
confidence: 99%
See 3 more Smart Citations
“…(11) ( 12) N -Sulfonylaldimines undergo Mannich-type addition to silyl enol ethers of ketones, giving β-amino carbonyl derivatives in up to 93% ee in the presence of a chiral ee ferrocene bearing S-and P -substituents complexed to copper(II). 29 β-Aminocarbonyl compounds have been prepared via Lewis base-catalysed Mannich reaction of TMS enol ethers and N -tosylaldimines, ArCH=N−Ts, with excellent de anti selectivity in some cases. 30 A zinc-bis(BINOL) complex has been employed to effect chemoselective enolate de formation from an α-hydroxy ketone (in the presence of an isomerizable imine) to give a Mannich-type product in high ee.…”
Section: The Mannich Reactionmentioning
confidence: 99%
“…77 de Non-activated imines have been pentafluorophenylated with (F 5 C 6 ) 3 SiF; protonation activates the imine, and chloride ions activate the silane. 78 Highly substituted amides (29) have been prepared in a three-component reaction of an imine, an acid chloride, and trialkylindium. 79 Proceeding under mild conditions and high metal efficiency, the 'alkyl' group on indium can also be aryl, heteroaryl, or vinyl.…”
Section: Iminium Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…27 The Carretero group developed a Mannich-type reaction of ketene silyl acetal or ketene silyl thioacetal with aldimines bearing a 2-thienylsulfonyl group on nitrogen by means of Cu(I)-Fesulphos (20) (Scheme 20). 28 2 . They found that the m-hydroxo complex were found to be good catalysts for the Mannich-type reaction of silyl enol ether with a-imino ester (Scheme 23).…”
Section: Introductionmentioning
confidence: 99%